THE ROLE OF YERSINIA PESTIS RESIDENT PLASMIDS PMT1, PCD1, AND PPCP1 IN THE PRODUCTION OF LIPOPOLYSACCHARIDE EXTRACELLULAR FORM - E. P. Sokolova; V. P. Zyuzina; G. V. Demidova; O. N. Podladchikova; V. A. Rykova; V. I. Tynyanova (Проблемы особо опасных инфекций, 2017)
Objective of the study is to investigate the role of resident plasmids pMT1, pCD1, and pPCP1 in the production of extracellular form of Yersinia pestis lipopolysaccharide (LPS).Materials and methods. The experiments have been performed using Y. pestis strain EV76 (pMT1, pCD1, pPCP1), carrying the whole plasmid set, as well as plasmid-free Y. pestis variant EV76 (pMT1-, pCD1-, pPCP1-), and isogenic clones, harbouring only one plasmid: Y. pestis EV76 (pMT1); Y. pestis EV76 (pCD1); Y. pestis EV76 (pPCP1). The presence of extracellular LPS in the incubation medium of Y. pestis EV76 cells has been confirmed by supernatant toxicity for laboratory animals and also by LAL-test reaction.Results and conclusions. It has been established that LPS extracellular form is produced by 37 °C Y. pestis EV76 cultures of the initial strain and its variants, carrying pMT1 or pPCP1 plasmid. Plasmid-free cultures and variant harbouring pCPP1 plasmid are deprived of such ability. The results of LAL-test has shown that the process of LPS separation from cell wall membrane into the environment is associated with translocation of proteins encoded by pMT1 and pCD1 plasmids and constitutes a natural form of existence of Y. pestis cells. The involvement of pCD1 plasmid in realization of the toxic potential of Y. pestis LPS has been established for the first time ever.